Inovação e cultura organizacional: um estudo dos elementos culturais que fazem parte de um ambiente inovador - Machado, Denise Del Prá Netto (2004)
In the last decade, innovation started to be considered a strategic theme in businesses administration. Although innovation is present in the whole history of man kind, and is pointed as a critical factor for obtaining competitive advantage in businesses, it is difficult know how to foment and motivate it. Studies about innovation and how to reproduce it in different organizations are still rare among scholars and researchers in Brazil. It happens due the fact that businesses see innovation as a source of competitive advantage and are not willing to show how to reproduce it. This situation was the motivation for this research, which intended to verify how an innovation atmosphere is constituted inside businesses, and which elements of organizational culture are linked to innovation. The subjects of this research were organizational actors that interact directly with innovation, as well as those that live the atmosphere and view the culture of the organization day by day. The research used intentional sampling, answered by 7 (seven) companies considered to be innovative in the market. The research was carried out with 30 (thirty) representatives in each company. The companies studied are all Brazilian, of several different industries, sizes and geographic location. The revenue and the number of employees are also different among them. This sampling diversity was deliberate, trying to discover similarities of culture characteristics among such different companies. The research was divided in two phases: diagnosis and validation. Qualitative and quantitative studies were carried out in 3 organizations during the diagnosis phase. The data obtained in this phase was validated (in the validation phase) with other 4 organizations. The innovative atmosphere was observed in the 7 organizations researched. Values, the faiths and presuppositions, the rites, rituals and ceremonies, the stories and myths, the taboos, the heroes, the communication and the artefacts and symbols are the elements that form the culture of the organization and were found related to innovation. Stand out of these elements “taboos”. Taboos constitute something that the people “do not agree nor disagree', i.e., they prefer not to speak about it. In the validation stage the same elements were found, with smaller incidence of the artefacts and symbols. The results confirm the research hypothesis that organizations that are innovative in their final result also possesses culture elements that propitiate and motivate the development of innovations.